The new CFO financial leadership manual - Bragg, Steven M. (Wiley Online Library., 2011)
"Today's Chief Financial Officer is faced with responsibilities that have become as diverse and dynamic as they are important. In addition to the management of day-to-day financial activities and the implementation of a long-term fiscal strategy, the CFO must also keep abreast of up-and-coming key issues such as electronic commerce, risk management, and outsourcing. These duties require both a thoughtful consideration of the changing nature of this job, as well as a reliable step-by-step guide to the nuts and bolts. New chapters to be covered in this edition include investor relations and risk management for foreign exchange and interest rates.This book is a reference work that CFOs and other financial managers can turn to get quick answers to questions that they have as well as to help them plan their financial strategy. The tentative contents is: (1) CFO's place in the corporation; (2) Financial strategy; (3) Tax strategy; (4) Information technology strategy; (5) Performance measurement systems; (6) Control systems; (7) Audit function; (8) Reports to the Securities and Exchange Commission; (9) Cost of capital; (10) Capital budgeting; (11) Other financial analysis topics; (12) Cash management; (13) Investing excess funds; (14) Obtaining debt financing; (15) Obtaining equity financing; (16) Initial public offering; (17) Investor relations; (18) Taking a company private; (19) Risk management: General; (20) Risk management for foreign exchange and interest rates; (21) Outsourcing the accounting and finance functions; (22) Mergers and acquisitions; (23) Employee compensation; (24) Bankruptcy"--